Environmental, Health and Economic Conditions during the COVID-19 Pandemic - Lamichhane, Dirga (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The spread of coronavirus disease 2019 (COVID-19), which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has evolved as a global pandemic and the disease has affected nearly every country and region. This pandemic has posed further threats to people due to the emergence of the number of novel SARS-CoV-2 strains with unknown original hosts. Since the start of the pandemic, COVID-19 has overwhelmed health systems worldwide, from crippling health resources to causing paradigms shifts in health care delivery. The various strategies taken to control viral transmission including testing process, quarantine and isolation have had dire psychological and financial implications on individuals and institutions. Furthermore, many countries have implemented lockdowns and other restrictions to curb the virus's spread resulted in disrupted formal education, unplanned fiscal costs on emergency reliefs, and decreased productivity. This Special Issue provides an avenue for authors from various disciplines to better understand the risk factors associated with the spread and severity of COVID-19 infections. It also provides information about the influence of COVID-19 and its countermeasures on local economies, the environment, and mental health. This Special Issue contains 11 research articles and one review.